(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Late-onset sepsis is a major cause of morbidity and mortality in very low birth weight (VLBW) neonates, with fungal infections, particularly Candida species, emerging as an important etiological agent. The incidence and outcome of neonatal candidemia vary across neonatal intensive care units, especially in high-risk VLBW infants. Methodology: This prospective observational study was conducted in the Department of Paediatrics, Sree Mookambika Institute of Medical Sciences, Kulasekharam, from March 2025 to February 2026. VLBW neonates (1.0–1.5 kg) with late-onset sepsis were included, while those with early-onset sepsis and birth weight <1.0 kg or >1.5 kg were excluded. Clinical features, laboratory data, and culture reports were analyzed to identify fungal sepsis. Statistical analysis was performed using Chi-square test and Fisher’s exact test, with p<0.05 considered significant. Results: Among VLBW neonates with late-onset sepsis, Candida sepsis was observed with male predominance (63.3%), though not statistically significant (p=0.63). A significant association was noted with birth weight (p=0.046). Common clinical features included hypothermia (70%), abdominal distension (90%), and feeding intolerance (90%). Mortality was high, with 36.7% deaths among culture-positive cases. Conclusion: Candida sepsis is a significant cause of late-onset sepsis in VLBW neonates with high mortality. Early recognition of clinical signs and timely management are essential to improve outcomes.